The Impact of Negative Content on the Cognitive Abilities of Class VIII Students at SMP Negeri 1 Mataram - Muh. Ilham Ependi; Nyayu Dian Permanu; Ulya Ristiana Zuhro; Lina Raehana; Reni Oktapiana; Rama Febrian Maulana (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to identify the impact of negative content on the cognitive abilities of grade VII students at SMP Negeri 1 Mataram. This study uses a qualitative descriptive method, with data collection through interviews, observations, and documentation. The subjects of the study were grade VIII students at SMP Negeri 1 Mataram. Negative content, such as false information, violence, and hate speech, can affect students' concentration and critical thinking skills. From interviews conducted with 76 students, the level of exposure to negative content and its impact on academic performance were determined. The results showed that most students experienced decreased concentration due to exposure to negative content and many students showed difficulty in critical thinking. Factors such as the duration of digital device use and lack of digital literacy were also found to influence the level of impact. This study emphasizes the importance of the role of teachers and parents in supervising students' content consumption, as well as the need for digital literacy education to improve the ability to sort information. Thus, it is hoped that students can reduce exposure to negative content and optimize their cognitive abilities to achieve better learning outcomes.